Evaluation of Professional Commitment Levels of Teacher Candidates - Murat Korucuk; Halil İbrahim Kaya (Mimbar Sekolah Dasar, 2023)
In this study, it is aimed to determine the commitment level of commitment to the teaching profession of teacher candidates enrolled in the 2021-2022 academic year pedagogical formation education certificate program. Moreover, it is also aimed to examine the situations of difference in the levels of commitment to the teaching profession of teacher candidates according to variables such as gender, field (social sciences, natural sciences, health sciences), university,  high school, income level, family residence, mother’s/father’s profession, and mother’s/father’s education status. The study was designed according to the survey model. For this reason, data were obtained from a large population. While the population consists of 267 teacher candidates enrolled in the pedagogical formation program in 2022 at a university in the east of Turkey, the sample consists of 216 teacher candidates determined by the simple random sampling method. The data collection tool used in the study is the “Teaching Profession Engagement Scale-TPES”. The study concludes that the professional commitment levels of pre-service teachers registered in the pedagogical formation program were high. Additionally, it is also revealed that the professional commitment of teacher candidates differs according to the variables (field, high school, mother's education level and mother's profession).